A Review of Road-killed Felids in Mexico - Gonzalez-Gallina, Alberto; Hidalgo-Mihart, Mircea G. (THERYA, 2018)
Six species of felids are distributed across Mexico and all are affected to a greater or lesser extent by the national highway network (377,660 km in length), but the magnitude of its impact on these species is unknown. Part of the issue is the scarce information available spread across the scientific literature, mammal collections records, environmental consultancies, and the local press. This work compiled the information available on road-killed felids in Mexico and organizes it systematically to identify potential data trends. We conducted a systematic search for records of verified felid roadkill events across Mexico reported in the scientific literature, mammal collections, online news and emails addressed to mammal -- particularly wild cat -- management/conservation specialists. First, felid roadkill records were entered and classified according to origin, i.e. source of information, and then classified according to the state where the event occurred. This information was used to explore the potential correlation between felid roadkill frequency and road density per state. Roadkill events were reported for all felid species, with a total of 115 records in 25 states: Herpailurus yagouaroundi, 21; Leopardus pardalis, 20; L. wiedii, 11; Lynx rufus, 50; Puma concolor, 5; and Panthera onca, 8. Most of the information came from mammal collections (40 records), followed by personal communications (25), and publications in local media (19), citizen science websites (10), peer-reviewed journals (9), non-governmental organizations (7), and government agencies (5). We found a significant correlation between road density and number of roadkill events recorded per state. Road density alone is insufficient to explain some geographic bias in felid roadkill data, which might instead be related to the appeal of a species, and to being recorded by people (scientists or otherwise) interested in this issue in a particular location. Acknowledging road mortality as an issue for felids in our country might contribute to identify and apply methods to improve data collection (citizen science) to develop preventive measures in our highways (wildlife crossing structures), particularly in wildlife high-risk areas.